An ultrafast approach for the syntheses of defective nanosized lanthanide perovskites for catalytic toluene oxidation. Issue 17 (6th August 2018) - Weng, Xiaole; Wang, Wang Long; Meng, Qingjie; Wu, Zhongbiao
Abstract : In this article, Sr 2+ and/or Fe 3+ -doped LaMnO3 perovskites were rapidly synthesized using supercritical water (sc-H2 O) in a continuous hydrothermal flow reactor. Abstract : In this article, Sr 2+ and/or Fe 3+ -doped LaMnO3 perovskites were rapidly synthesized using supercritical water (sc-H2 O) in a continuous hydrothermal flow reactor. Nanosized perovskites (6–45 nm) with defective structures were obtained, which led to high surface areas (28–67 m 2 g −1 ) and enriched defects. After being subjected to catalytic toluene oxidation, La0.9 Sr0.1 Mn0.9 Fe0.1 O3 exhibited superior activity with T 50 ( i.e., the temperature of 50% toluene conversion) at approximately 213 °C, T 90 ( i.e., the temperature of 90% toluene conversion) at approximately 236 °C, and the reaction rate constant, k, at 1.47 mL g −1 s −1 (at 180 °C). Such activity was even comparable to that of some noble metal catalysts. H2 -TPR, O2 -TPD and 18 O2 -TPSR analyses suggested that both the Langmuir–Hinshelwood and Mars–van Krevelen mechanisms are involved in such a toluene oxidation process, where the dissociation of gaseous oxygen ( via the surface oxygen vacancies) and the diffusion of mobile lattice oxygen (to the catalyst surface) in the lanthanide perovskites played a crucial role in determining their toluene oxidation efficiencies. This explained why La0.9 Sr0.1 Mn0.9 Fe0.1 O3 that has enriched surface oxygen vacancies and high lattice oxygen mobility (both originating from the structural distortion in sc-H2 O reaction) could yield a remarkable performance in catalytic toluene oxidation.